ANALISIS PENGARUH BUDAYA ORGANISASI TERHADAP KINERJA PEGAWAI PADA BAGIAN KEUANGAN DAN PERLENGKAPAN SEKERTARIAT DAERAH KABUPATEN JAYAPURA - Abraham Rieuwpassa (Sekolah Tinggi Ilmu Ekonomi Port Numbay Jayapura, 2021)
This study aims to determine whether organizational culture has a significant effect on employee performance in the Finance and Equipment Section of the Regional Secretariat of Jayapura Regency. This shows that the t value of the organizational culture variable (X) is 6.879 > t table 1.713 with a significance level of 0.000 < 0.05. Thus the hypothesis is suspected that the organizational culture variable (X) has an effect on employee performance at the Regional Secretariat of Jayapura Regency. Then the correlation coefficient (R) of 0.815 indicates that the organizational culture variable (X) has a strong relationship to the performance of employees in the Finance and Equipment Section of the Regional Secretariat of Jayapura Regency. While the coefficient of determination R2 of 0.663 means that there is an influence of organizational culture on employee performance in the Finance and Equipment Section of the Regional Secretariat of Jayapura Regency of 0.663 or 66.3% while the remaining 33.7% is influenced by other variables not examined.